Spatial Arrangement between Relocation and Change of River Flow to The Jragung Border Settlement - Rahma Alia; Baidhowi (Law Research Review Quarterly, 2026)
This study analyzes community organizations located in the buffer zone of the Jragung River in Demak Regency, which is legally a protected area under Indonesian spatial planning and water management regulations. The primary issue discussed is the continued presence of these organizations in the river boundary area despite clear laws, specifically those stipulated in Demak Regency Regulation Number 6 of 2011, Article 83 paragraph (3), which prohibits development within the river buffer zone, and Law Number 1 of 2011, Article 140, which restricts housing development outside the designated community organization area. These regulations stipulate a minimum distance of five meters from river embankments in areas outside the urban zone. This study aims to explore solutions to these problems. It uses an empirical legal method with a descriptive approach. The legal analysis focuses on the laws and regional regulations governing the river buffer zone, while empirical data is obtained through field observations and interviews with residents living along the Jragung River. Findings indicate that organizations in the river buffer zone developed gradually due to inherited land ownership, economic constraints, strong social continuity with the settlement, and weak government oversight and legal dissemination. While relocation provides hydrological and ecological benefits, it also poses significant social and economic challenges for affected communities. In contrast, river engineering measures, such as river channel straightening and embankment construction, are considered more feasible in the study area because they reduce disaster risk without causing significant social disruption.